A Study on The Students’ Motivation and Perception in E-Learning English (Case Study at Vocational School in Banyuwangi) in The Covid-19 Pandemic - Mila Tresna; Dzulfikri Dzulfikri; Mutmainah Mustofa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study aimed to know and reveal the deep students’ perception and motivation through E-Learning English during pandemic. E-Learning was the only option such a new normal in learning process during Covid-19 outbreak. E-Learning is a teaching and learning system that utilizes electronic media specifically the internet. This model of learning system makes it easy for teachers and students because learning can be carried out anytime and anywhere so that will be many problem and challenges for them through new normal learning that can affect their motivation and perception. In this study, the researcher administered online questionnaire through google form to find out their perception and motivation and conducted interviews to find out how deep their perspective about the experience in E-Learning procces that did not find the information in questionnaire. The study findings showed that participants’ perceive this E-Learning English both positive and negative insights as indicated by their questionnaire and interview results. It is recommended that the teachers should be more attractive in the E-Learning classroom and the government as the central controller should create a policy that ease students and teachers conduct E-Learning activities.